Personal Establishment and Accomplishment of Public Service Values - Mirko PEČARIČ (Transylvanian Review of Administrative Sciences, 2013)
Public objectives are mostly developed within public administrations, which despite apparent Weberian rationality work mainly evolutionarily, i.e. by imitation of what already works in other areas and what randomly brings good results. The rule of law that is fundamental to the Western democratic order cannot work without morality and legal values. If we want workable values, we must understand them at their core, which is not the domain of law. The starting point is an individual who operates primarily on the basis of his personal characteristics regardless of all the present theories of the public administration. Entering into the unknown with full preparedness for the changes will be the motto of the future public administration. We are much closer to such a stance if we know how the public service values are really established and implemented.